PHARMACOTHERAPY QUALITY IN PATIENTS WITH ARTERIAL HYPERTENSION OBSERVED IN PRIMARY CARE PRACTICE. HYPERTENSION REGISTER DATA - O. M. Posnenkova; A. R. Kiselev; V. I. Gridnev; V. A. Shvartz; P. Ya. Dovgalevsky; E. V. Oschepkova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To assess (on the basis of Russian national guidelines on arterial hypertension (HT), 2004) quality of pharmacotherapy measures among hypertensive patients observed in primary care practice. Material and methods. Data on 12 604 patients with HT (7 819 women, 4 785 men, aged 59.5±12.0 years) from 13 regions of Russia observed in primary care units during 2007 were enrolled in the study. Compliance with recommendations on decision making about pharmacotherapy need (risk category assessment) and adequacy were evaluated. Results. 64% of patients with HT had no drug prescriptions in their outpatient card in 2007. 4 880 patients from 12 604 enrolled HT patients (38.7%) had all data necessary for risk assessment. 3920 patients (31% of the whole studied group) had pharmacotherapy indications (high or very high risk). Only 819 HT patients (6.5% of the whole number of enrolled patients) had antihypertensive pharmacotherapy completely corresponding to their clinical status. Conclusion. The quality of pharmacotherapy measures carried out in primary care practice during 2007 did not conform to HT guidelines.